Simulasi Difraksi Fraunhofer Menggunakan Media Spreadsheet dan GNU Octave Sebagai Alternatif Pembelajaran dimasa Pandemi - Aditya Yoga Purnama; Heru Kuswanto; Syella Ayunisa Rani; Himawan Putranta; Puji Hariati Winingsih (Universitas Hamzanwadi, 2021)
The title of this paper is Fraunhofer diffraction simulation using spreadsheet and GNU octave media as an alternative for learning during the pandemic. This paper aims to present an alternative to distance learning during the COVID-19 pandemic by using simulations using spreadsheets and GNU Octave media.Optical practicum in physics laboratories can not be done during pandemics. So the solution that can be offered is to use simulations on optical subjects of diffraction material. In the simulation making activities students can learn and explore about the phenomenon of diffraction. Simulations using the equations used in the research of Zhanget al. in 2013.This simulation is used to visualize the effect of variations in different parameters such as wavelengths and gap widths in Fraunhofer diffraction patterns. This paper has successfully simulated Fraunhofer's diffraction using spreadsheets as well as GNU Octave. This distance learning allows students to develop fraunhofer computational computational skills and conceptual understanding of diffraction